Artemisinin combination therapy mass drug administration in a setting of low malaria endemicity: programmatic coverage and adherence during an observational study in Zanzibar - Ali, Abdullah S. (Malar J, 2017)
BACKGROUND: Mass drug administration (MDA) appears to be effective in reducing the risk of malaria parasitaemia. This study reports on programmatic coverage and compliance of MDA using artemisinin-based combination therapy (ACT) in four shehias (smallest administration unit) that had been identified as hotspots through Zanzibar’s malaria case notification surveillance system. METHODS: Mass drug administration was done in four shehias selected on the basis of: being an established malaria hot spot; having had mass screening and treatment (MSaT) 2–6 weeks previously; and exceeding the epidemic alert threshold of 5 cases within a week even after MSaT. Communities were sensitized and MDA was conducted using a house-to-house approach. All household members, except pregnant women and children aged less than 2 months, were provided with ACT medicine. Two weeks after the MDA campaign, a survey was undertaken to investigate completion of ACT doses. RESULTS: A total of 8816 [97.1% of eligible; 95% confidence interval (CI) 96.8–97.5] people received ACT. During post MDA surveys, 2009 people were interviewed: 90.2% reported having completed MDA doses; 1.9% started treatment but did not complete dosage; 4.7% did not take treatment; 2.0% were absent during MDA and 1.2% were ineligible (i.e. infants <2 months and pregnant women). Main reasons for failure to complete treatment were experience of side-effects and forgetting to take subsequent doses. Failure to take treatment was mainly due to fear of side-effects, reluctance due to lack of malaria symptoms and caregivers forgetting to give medication to children. CONCLUSION: Mass drug administration for malaria was well accepted by communities at high risk of malaria in Zanzibar, with high participation and completion rates. Further work to investigate the potential of MDA in accelerating Zanzibar’s efforts towards malaria elimination should be pursued.